Effect of direct and indirect transfer status on trauma mortality in sub Saharan Africa. Issue 5 (May 2016) - Boschini, Laura P.; Lu-Myers, Yemeng; Msiska, Nelson; Cairns, Bruce; Charles, Anthony G.
Abstract: Introduction: Traumatic injuries account for the greatest portion of global surgical burden particularly in low- and middle-income countries (LMICs). To assess effectiveness of a developing trauma system, we hypothesize that there are survival differences between direct and indirect transfer of trauma patients to a tertiary hospital in sub Saharan Africa. Methods: Retrospective analysis of 51, 361 trauma patients within the Kamuzu Central Hospital (KCH) trauma registry from 2008 to 2012 was performed. Analysis of patient characteristics and logistic regression modelling for in-hospital mortality was performed. The primary study outcome is in hospital mortality in the direct and indirect transfer groups. Results: There were 50, 059 trauma patients were included in this study. 6578 patients transferred from referring facilities and 43, 481 patients transported from the scene. The indirect and direct transfer cohorts were similar in age and sex. The mechanism of injury for transferred patients was 78.1% blunt, 14.5% penetrating, and 7.4% other, whereas for the scene group it was 70.7% blunt, 24.0% penetrating, and 5.2% other. Median times to presentation were 13 (4–30) and 3 (1–14) h for transferred and scene patients, respectively. Mortality rate was 4.2% and 1.6% for indirect and direct transfer cohorts, respectively. A total of 8816 patients were admitted of which 3636 and 5963 were in the transfer and scene cohort, respectively. After logistic regression analysis, the adjusted in-hospital mortality odds ratio was 2.09 (1.24–3.54); P  = 0.006 for indirect transfer versus direct transfer cohort, after controlling for significant covariates. Conclusions: Direct transfer of trauma patients from the scene to the tertiary care centre is associated with a survival benefit. Our findings suggest that trauma education and efforts directed at regionalization of trauma care, strengthening pre-hospital care and timely transfer from district hospitals could mitigate trauma-related mortality in a resource-poor setting.